Mathematical models for network card simulation and their empirical validations - Nurika, O. (Institute of Electrical and Electronics Engineers Inc., 2016)
Network simulations mostly focus on protocol observation, development, and prediction. However, newly developed protocol will take time to become standard and be implemented on network devices. A faster way of network improvement is to optimize existing network card parameters, because they are generic and protocol-independent. In this paper, we propose mathematical models to represent network card parameters, thus their optimal configuration can be predicted, which then will accelerate the reduced network speed caused by unoptimized network hardware. The simulation gaps that we fulfill are the inclusion of transmission size, packet polling based on timer, and packet polling based on watermark or packet capture threshold. The results generated and their validations show the accuracy of our models. Â© 2015 IEEE.